Numerous Iron-Rich Particles Lie on the Surface of Erionite Fibers from Rome (Oregon, USA) and Karlik (Cappadocia, Turkey). (19th August 2015) - Croce, Alessandro; Allegrina, Mario; Rinaudo, Caterina; Gaudino, Giovanni; Yang, Haining; Carbone, Michele
Abstract: Erionite samples from Rome, Oregon (USA) and Karlik, Cappadocia (Turkey) were analyzed by environmental scanning electron microscopy (E-SEM) coupled with energy-dispersive spectroscopy (EDS) to verify the chemical composition of this mineral phase, and the presence of iron in particular. By means of backscattered electron images, a large number of particles/grains were observed on the surface of the erionite fibers from both locations. The particles were found to be micrometric on samples from Rome and submicrometric on samples from Karlik, and always lighter than the hosting crystal in appearance. In different areas of the same fiber or bundle of fibers, several EDS spectra were recorded. Iron was detected only when a light particle was lying in the path of the electron beam. Iron was never identified in the EDS spectra acquired on the flat erionite surface. The results from E-SEM/EDS were confirmed by micro-Raman spectroscopy, showing bands ascribing to hematite—Fe2 O3, goethite—FeO(OH), or jarosite—KFe3 3+ (SO4 )2 (OH)6 when the laser beam was addressed on the light particles observed on the fiber surface. The evidence that iron is on the surface of erionite fibers, rather than being part of the crystalline structure, may be relevant for the carcinogenic potential of these fibers.